Lifelong learning as a pillar of institutional and human development - Ab Rahman, Farah Adilla (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s fast-changing world, lifelong learning is a strategic necessity that supports professional adaptability, institutional resilience, and inclusive development. Defined as the continuous, self-directed acquisition of knowledge and skills through formal, non-formal, and informal experiences, it enables individuals to stay agile and links personal growth to institutional transformation (Khasnabis et al., 2010). Lifelong learning spans all career stages, from students to senior professionals, though engagement is influenced by factors such as age, gender, discipline, and education level (Babenko et al., 2017; Thwe & Kálmán, 2023). To foster continuous learning, institutions must create environments that promote curiosity, equity, innovation, and digital adaptation, addressing gaps in learning communities, motivation, and pedagogy to build sustainable learning cultures.